EFL in-service teachers' self-reported perspectives on English language assessment (2022)
The purpose of the following quantitative non-experimental and cross-sectional research study is to examine in-service teachers’ perceived views, skills, and practices towards the assessment of the English language. A sample of 315 in-service Chilean teachers took part in this study and data was collected through the Classroom Assessment Practices and Skills (CAPS) scale. Descriptive statistics and exploratory factor analysis were used to analyze the results. Findings indicated that in-service teachers perceived monitoring students´ learning as the purpose of assessment and agreed on the importance of diagnostic exams. Participants also considered making sure tests included all content taught and the use of assessment results for planning, as strong skills. Finally, the in-service teachers´ most frequent practices were associated with the design and feedback of assessment instruments. Keywords: in-service teachers´ perceptions, language assessment literacy, English language assessment, assessment skills, classroom assessment practices